2012
DOI: 10.1074/jbc.m111.325670
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and Distribution of Klothoβ (KLB) and Fibroblast Growth Factor Receptor-1 (FGFR1) in Living Cells Reveal the Fibroblast Growth Factor-21 (FGF21)-induced Receptor Complex

Abstract: Background: FGFR1c and KLB form an ill-defined FGF21 signaling complex. Results: FGFR1c competes with galectin for binding to KLB. KLB and FGFR1c interact in a 1:1 heterocomplex, and subsequent addition of FGF21 induces FGFR1c dimers. Conclusion: KLB and FGFR1c activity and dynamics suggest that the galectin lattice modulates FGF21 signaling. Significance: The galectin lattice is a novel target to potentiate therapeutic effects of FGF21.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 39 publications
3
31
0
Order By: Relevance
“…There has been a previous attempt to study behaviors of C-terminally tagged full-length FGFR1c and KLB in the context of plasma membrane using a fluorescent imaging-based method ("the number and brightness analysis") in living HeLa cells (53). This study by Ming et al (53) has observed that fulllength FGFR1c molecules exist as dimers in the absence of ligands, consistent with our conclusion.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…There has been a previous attempt to study behaviors of C-terminally tagged full-length FGFR1c and KLB in the context of plasma membrane using a fluorescent imaging-based method ("the number and brightness analysis") in living HeLa cells (53). This study by Ming et al (53) has observed that fulllength FGFR1c molecules exist as dimers in the absence of ligands, consistent with our conclusion.…”
Section: Discussionsupporting
confidence: 90%
“…By combining SNAP and ACP tags with TR-FRET technology, we demonstrate here that, like EGFR, full-length FGFR1 can efficiently form ligand-independent oligomers, most likely dimers, on the cell surface. This confirms the previously proposed but rather controversial idea that FGFR1 forms preformed dimers in the absence of ligand (48,53). Structurefunction analysis supports the role for TMD and TKD, rather than ECD, in ligand-independent FGFR1 dimerization.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Cellular responsiveness to FGF21, either from the circulation or from autocrine/paracrine action, is determined by the presence in the cell membrane of FGF receptors (FGFRs) and, especially, of the co-receptor β-Klotho. FGF21 has a low affinity for FGFRs (FGFR1-4), which are ubiquitously distributed, and requires the formation of the ternary complex, FGF21-FGFR-β-Klotho (1:2:1), to exert its actions (Ming et al, 2012). Among FGFR subtypes, FGFR1 appears to play a predominant role (Adams et al, 2012;Kuroso et al, 2007;Yang et al, 2012).…”
Section: Fgf21 Synthesis and Actionmentioning
confidence: 99%
“…It is synthetized mainly in liver [31] but also in white [32] and brown [18] adipose tissue, skeletal muscle [33], heart [34], and β cells [12]. Action of FGF21 is through cell membrane receptor FGFR1c and β-Klotho interaction ( Figure 1) [35][36][37]. Intracellular signaling is then activated through phosphorylation of FGFR substrate 2 α (FRS2 α), extracellular response kinase 1/2 (ERK1/2), and Akt (protein kinase B) pathways [38,39].…”
Section: Fibroblast Growth Factor 21 (Fgf21)mentioning
confidence: 99%